Can a case be made for “unlearning” in the study of religions? - Kim Knott (Approaching Religion, 2024)
The concept of “unlearning” has been positively endorsed in both self-help literature and organizational research, but has yet to be discussed in the study of religions. Is there room for it in the conceptual space of religious socialization, pedagogy and spiritual seeking? Where does it occur in the spiritual journey, and what is its purpose? From the perspective of social learning, and drawing on a definition and model from organizational studies, the case for “unlearning” is considered with reference to those leaving religion. Addressing research gaps identified by organizational-studies scholars, I consider how leavers experience the process of freeing themselves from previously held beliefs, practices and commitments. What is revealed is an iterative and emotionally fraught process in which even voluntary religious leavers struggle to move on, often feeling powerless, even coerced by others. Whilst there is a broad fit between the basic process model of unlearning and what leavers experience, that is not the full story. Furthermore, questions remain about whether “unlearning” is a necessary or suitable concept, not least because it is rarely used by scholars of religion or practitioners themselves, all of whom prefer other terms.